The impact of institutional quality on ipos oversubscription: evidence in Malaysia - Koh, Yen Shin (2019)
The major purpose of this study is to examine the impact of institutional quality on oversubscription of initial public offerings (IPOs) listed in Bursa Malaysia from period of 2000 to 2016. This study exists of six controls variable for controlling the institutional quality on oversubscription. Numerous studies have examined the relationship between institutional quality and oversubscription on IPOs underpricing. This study fills the gap to determine the institutional quality on oversubscription as previous studies prove the oversubscription is significant to underpricing. The six dimension of institutional quality collected from World Governance Indicators (WGI) which consists of voice and accountability, government effectiveness, political stability and absence of violence/terrorism, regulatory quality, rule of law, and control of corruption. The information asymmetry and signaling theory are employed to illustrate the relationship of institutional quality to oversubscription. This study employs cross-sectional multiple regression analysis to test for its entire hypothesis. Analyzing the data of 392 IPOs in Malaysia, the result reveals that voice and accountability, and control of corruption are positive significant to oversubscription while regulatory quality is negative significant on oversubscription. However, government effectiveness, political stability and rule of law show insignificant to oversubscription. The GDP growth rate, firm size and IPOs offer price significant influence the oversubscription. This study could contribute to benefit investors when making investment decision. The results may alert the regulators to implement the sound policies to enhance the IPO market. Future research could examine the institutional quality on oversubscription involve in Asian region, developing and developed countries instead focus in Malaysia.